Creep Fracture Characteristics and the Constitutive Model of Salt Rock under a Coupled Thermo-Mechanical Environment. (24th August 2022) - Wang, Zhixia; Liang, Xufeng; Guangwu, Xue; Meng, Tao; Zhang, Jigang
Abstract : The fracture extension characteristics of salt rocks under creep play an important role in the long-term safety and stability assessment of underground compressed air storage reservoirs. To study the fracture evolution characteristics of salt rock with time, the present study modified the Charles creep fracture intrinsic model and calibrated the A and n of the fracture extension coefficient parameters by creep fracture experiments with a constant stress rate loading method for salt rock under different temperature conditions. Finally, the modified Charles model was embedded into PFC (particle flow code) to simulate the fracture of salt rock numerically and the results were verified theoretically. The results show that (1) the fracture extension rate is related to the parameters A and n in addition to the stress intensity factor; (2) both n and A gradually decrease with the increase of temperature, and an decrease of n and A represents the decrease of fracture creep extension rate; and (3) the longer the initial fracture length of the specimen, the smaller the fracture time. The results of this study can provide theoretical guidance for evaluating the confinement of underground compressed air storage reservoirs.